Effects of alkanolamine solvents on the aggregation states of reactive dyes in concentrated solutions and the properties of the solutions. Issue 18 (16th March 2021) - Cao, Chuangui; Zhao, Zhihui; Qi, Yong; Peng, Hui; Fang, Kuanjun; Xie, Ruyi; Chen, Weichao
Abstract : The solvent, DEA, reduces the dye aggregation that may be caused by the weak hydrogen bonding and relatively smaller steric hindrance effect. Abstract : The aggregation of dyes is a common phenomenon in solutions, particularly concentrated solutions, which seriously affects the dyeing and printing processes. In this study, the effects of alkylamine solvents on the reactive dye aggregation behavior in highly concentrated solutions was studied. Typical cases were conducted with two slightly toxic and environmentally friendly solvents, namely diethanolamine (DEA ) and triethanolamine (TEA ), and two reactive dyes, namely C. I. Reactive Red 218 (R-218 ) and C. I. Reactive Orange 13 (O-13 ). Aggregation states were studied by ultraviolet-visible (UV-Vis) absorption spectroscopy, Gaussian-peak-fitting method and fluorescence spectroscopy. The results showed that both the additives DEA and TEA could reduce the dye aggregation because the solvents, DEA and TEA, can break the iceberg structure and allow easy entry of the molecules into the dye aggregates. Also, the disaggregation caused by DEA was higher as compared with TEA, which may be caused by the weaker hydrogen bond and the relatively smaller steric hindrance effects of DEA . The schematic of disaggregation between R-218 and DEA was also discussed. For R-218, the dimers were disaggregated to monomer, while the higher-ordered aggregates were disaggregated to trimers and dimers for O-13 . Moreover, physical properties such as viscosity and surface tension of the solutions were measured. This investigation is instructive for the further dyeing progress with organic bases in the textile industries.